Fipronil and its metabolites in a tropical estuary: multi-compartment distribution, trophic transfer, and risk assessment - Yu-Han Xie; Can Huo; Zhi-Yan Wang; Shan-Shan Yao; Heng-Xiang Li; Yu Zhong; Xiao-Ping Huang; Xiang-Rong Xu (Marine Environmental Research, 2026)

Seasonal hydrochemical variations of a regulated river in the North China Plain: mechanisms and implications for chemical weathering - Xi Yang; Tao-Tao Ji; Zhi-Yuan Zhang; Rong-Tao Ma; Xiao-Wei Jiang (Journal of Hydrology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Disturbance-observer-augmented control barrier functions for safe multi-spacecraft formation - Xiao-Ning Shi; Dalin Rong; Di Zhou; Zhi-Gang Zhou (Advances in Space Research, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Integrated metabolomic and transcriptomic analyses reveal that pectin metabolism mediates texture divergence in grape berries - Zhi-Meng Gan; Xiao-Yan Ai; Yong Liu; Wei Zhu; Yang Zhang; Hui-Liang Wang; Fu-Rong Wang; Xiao-Dong Hou; Hua-Ping He; Lin-Zhong Gong (Postharvest Biology and Technology, 2026)

Functional characterization of a canonical C-type lectin from Mytilus coruscus: Roles in innate immunity and feeding processes - Ying-rong Jin; Chuan-yue Chen; Ze-kai Wang; Pan Qin; Zhi Liao; Xiao-lin Zhang; Xiao-jun Yan (Fish & Shellfish Immunology, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Investigation of the Shallow Structure of the Hami Basin Northern Margin Fault Using Comprehensive Geophysical Methods - Guang-hong Ju; Xiao-dong He; Rong-ying Zheng; Yan-ling Liu; Jun-qi Duan; Jun Shen; Zhi-tao Gao (Applied Geophysics, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

High-efficiency immobilization of soil available cadmium by chicken manure and its derivatives: Roles of chemical and microbial property - Zhi-Wen Hu; Feng Jiang; Fei Huang; Heng Wang; Qian-Jun Liu; Xiao Zhou; Ming-Zhi Huang; Peng Wang; Rong-Bo Xiao (Journal of Environmental Chemical Engineering, 2025)

A new sesquiterpene from endophytic fungus Colletotrichum sp. B-89 - Ke-tao Zhang; Bing Zhang; Zhi-pu Huang; Yu-xiao Xu; Xiao-rong Xu; Si-heng Li; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2025)

Monitoring-based analysis of the responses of upper structure and tunnel lining during shield tunneling with pile cutting - Zhi-Xiong Liu; Xiao-Wei Ye; Ke Song; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

1DCNN-based prediction methods for subsequent settlement of subgrade with limited monitoring data - Sen-Lin Xie; Anfeng Hu; Meihui Wang; Zhi-Rong Xiao; Tang Li; Chi Wang (European Journal of Environmental and Civil Engineering, 2025)

Isolation, characterization and biological activities of phenolics from the roots bark of Morus alba - Min Tan; Xiao-Cong Liu; Dan Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Phytochemistry, 2025)

Combination of herbal extracts regulates growth performance, liver and intestinal morphology, antioxidant capacity, and intestinal microbiota in Acrossocheilus fasciatus - Yi Ting Shen; Zhi Li Ding; Xiao Yan Wang; Wen Qi Chen; Rong Xing Xia; Shun Yang; Hui Fei (Aquaculture, 2025)

Quantitative mechanisms for the Cd2+ adsorption increased by sewage-sludge biochar but decreased by rice-straw biochar after melamine modification - Zi-Xuan Yin; Yun-Yi Zhang; Jia-Xin Liu; Fei Huang; Qian-Jun Liu; Ming-Zhi Huang; Rong-Bo Xiao; Guo-Yi Gao; Tian-Zhen Lan; Xiao Zhou (Journal of Environmental Chemical Engineering, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Analysis of two-dimensional consolidation behavior of soils under cyclic loading considering exacerbated tunnel leakage - Sen-Lin Xie; An-Feng Hu; Zhi-Rong Xiao; Mei-Hui Wang; Xun-Jian Hu; Gabriele Della Vecchia; Stefano Mariani (Computers and Geotechnics, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Composition of Sphagnum palustre L. extracts using different extraction methods - Zhi Wu; Zheng-Yi Hong; Yang Xu; Dai-Rong Wang; Qing-Bin Han; Ping Liu; Xiao-Rong Liu; Lan-Yue Zhang (Natural Product Research, 2024)

A new simple index for characterizing the labile heavy metal concentration in soil by diffusive gradients in thin films technique - Yang-xiao-xiao Shi; Hai-rong Xu; Jia Shen; Lin-yu Guo; Jing Yan; Jun Jiang; Zhi-neng Hong; Ren-kou Xu (Environmental Pollution, 2024)

A new 1,4-benzoxazine derivative produced by endophytic Colletotrichum gloeosporioides B-142 - Bing Zhang; Zhi-pu Huang; Yu Si; Ke-tao Zhang; Xiao-rong Xu; Jian-hong Chen; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Two calcium-based metal organic frameworks with long afterglow as anticounterfeiting materials - Rong-Hui Shi; Zhi-Qiang Long; Fanan Wang; Ling-Zhu Gong; Xiao-Ying Lin; Gui-Lin Zhuang; Dong-Fei Lu (Chemical Engineering Journal, 2024)

Chemical constituents of the leaves of Coriaria nepalensis and their chemotaxonomic significance - Min Tan; Xiao-Lan Chen; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

Fabrication of a novel antioxidant emulsifier through tuning the molecular interaction between soy protein isolates and young apple polyphenols - Zhi Chao Song; Huan Zhang; Peng Fei Niu; Lin Shan Shi; Xue Yan Yang; Yong Hong Meng; Xiao Yu Wang; Tian Gong; Yu Rong Guo (Food Chemistry, 2023)

Design of atomic cobalt selenide-doped sulfurized polyacrylonitrile cathode with enhanced electrochemical kinetics for high performance lithium-SPAN batteries - Zhi-Qiang Xu; Rong Zou; Wen-Wu Liu; Guang-Long Liu; Yun-Shou Cui; Yi-Xiao Lei; Ya-Wen Zheng; Wen-Jun Niu; You-Zhi Wu; Bing-Ni Gu; Ming-Jin Liu; Fen Ran; et al. (Chemical Engineering Journal, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

Geochemical behaviors of uranium and thorium during weathering and pedogenesis of carbonate rock: constraint from their speciation - Qiang Ma; Bing-jie Zhou; Zhi-gang Feng; Xiao-long Wang; Rong Chen; Pei-shan Li; Chong Huang (Environmental Science and Pollution Research, 2023)

A new δ-valerolactone produced by marine Streptomyces sp. YIM 13591 - Bing Zhang; Yu-ying Zhao; Zhi-pu Huang; Ke-tao Zhang; Xiao-rong Xu; Qing Zhao; Xiao-mei Zhang (Natural Product Research, 2023)

Phylogenomic insights into the origin and evolutionary history of evergreen broadleaved forests in East Asia under Cenozoic climate change - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Cen Guo; Xin‐Yu Du; Shui‐Yin Liu; Xiang‐Qin Yu; Xiao‐Guo Xiang; Jun Rong; Bing Liu; Zhi‐Fang Liu; Peng‐Fei Ma; De‐Zhu Li (Molecular Ecology, 2023)
The evergreen versus deciduous leaf habit is an important functional trait for adaptation of forest trees and has been hypothesized to be related to the evolutionary processes of the component species under paleoclimatic change, and potentially reflected in the dynamic history of evergreen broadleaved forests (EBLFs) in East Asia. However, knowledge about the shift of evergreen versus deciduous leaf with the impact of paleoclimatic change using genomic data remains rare. Here, we focus on the Litsea complex (Lauraceae), a key lineage with dominant species of EBLFs, to gain insights into how evergreen versus deciduous trait shifted, providing insights into the origin and historical dynamics of EBLFs in East Asia under Cenozoic climate change. We reconstructed a robust phylogeny of the Litsea complex using genome‐wide single‐nucleotide variants (SNVs) with eight clades resolved. Fossil‐calibrated analyses, diversification rate shifts, ancestral habit, ecological niche modelling and climate niche reconstruction were employed to estimate its origin and diversification pattern. Taking into account studies on other plant lineages dominating EBLFs of East Asia, it was revealed that the prototype of EBLFs in East Asia probably emerged in the Early Eocene (55–50 million years ago [Ma]), facilitated by the greenhouse warming. As a response to the cooling and drying climate in the Middle to Late Eocene (48–38 Ma), deciduous habits were evolved in the dominant lineages of the EBLFs in East Asia. Up to the Early Miocene (23 Ma), the prevailing of East Asian monsoon increased the extreme seasonal precipitation and accelerated the emergence of evergreen habits of the dominant lineages, and ultimately shaped the vegetation resembling that of today.

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

Transcriptome sequencing and metabolite analysis reveal the single and combined effects of microplastics and di-(2-ethylhexyl) phthalate on Peneaus vannamei - Qiang-Qiang Shi; Xiao-Qian Zhang; Ze-Ming Zhang; Ning-Bo Wang; Hua Liu; Rong-Rong Zhang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Science of The Total Environment, 2023)

Hollow urchin-shaped NCM811 ternary-structure for high rate charge/discharge capability and efficient CO2 adsorption - Fan-Ming Yang; Xiao-Yao Zhou; Xi-Da Li; Zhi-Cheng Yi; Rong Feng; Guo-Wen He (Journal of Environmental Chemical Engineering, 2023)

Chemical constituents from the root bark of Morus alba and their chemotaxonomic significance - Xiao-Cong Liu; Xuan-Qin Chen; Rong-Tao Li; Zhi-Jun Zhang (Biochemical Systematics and Ecology, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Physiological and transcriptome analysis of Mytilus coruscus in response to Prorocentrum lima and microplastics - Xiao-wen Tang; Rong Yu; Mei-hua Fan; Zhi Yang; Zhi Liao; Zong-xin Yang; Chen-ying Xie; Yu-kun Xuan; Jian-xin Wang; Xiao-lin Zhang; Xiao-jun Yan (Frontiers in Marine Science, 2022)
Nowadays, diarrheic shellfish toxicity (DSP) toxin and microplastics (MPs) are commonly found in coastal waters worldwide. Due to their widespread use, their persistence and toxicity, they may induce adverse effects on Mytilus coruscus . However, the underlying toxic mechanisms of DSP and MPs on M. coruscus remain unclear. This study explored the physiological index and transcriptome change of the digestive gland of adult M. coruscus exposed for 3 days to polystyrene (PS) MPs (0.2 mg/L, 90-100 μm) and Prorocentrum lima alone or in combination. The results showed that the CAT activity and MDA content significantly increased, respiration rate and feeding rate significantly decreased. The combination of MPs and P. lima caused more structural damage to the rough surface endoplasmic reticulum and mitochondria in the digestive glands of M. coruscus . The transcriptome analysis showed that 485 and 220 genes were up- and down-regulated, respectively, after exposure to P. lima ; 1,989 up-regulated DEGs and 1,098 down-regulated DEGs were identified after exposure to MP treatment, and 1,004 up-regulated DEGs and 664 down-regulated DEGs were identified after exposure to the combination of P. lima and MPs. The DEGs were mainly enriched in the lysosome, mRNA surveillance pathway, carbon metabolism, the mTOR signaling pathway, the complement and coagulation cascades, and the TNF signaling pathway. The MP, P. lima exposure mainly induced the expression of RNA-binding protein musashi, serine/arginine repetitive matrix protein 1, low affinity immunoglobulin epsilon Fc receptor, toll-like receptor 2, caspase 7, calmodulin, E3 ubiquitin-protein ligase, serine/threonine-protein kinase PRP4, glutathione S-transferase, and heat shock 70 kDa protein. MPs and P. lima poison mainly influence the expression of RNA transport, immune related gene, apoptosis, signal related gene, and antioxidant gene change. The combination of MPs and P. lima has a synergistic toxic effect. This study provides a new insights into its physiological and molecular responses of M. coruscus to MPs and P. lima toxic exposure.

Infestation and distribution of chigger mites on Confucian white-bellied rat (Niviventer confucianus) in Southwest China - Yan-Ling Chen; Xian-Guo Guo; Wen-Yu Song; Tian-Guang Ren; Lei Zhang; Rong Fan; Cheng-Fu Zhao; Zhi-Wei Zhang; Wen-Ge Dong; Xiao-Bin Huang (Biologia, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Effects of simulated drought stress on carotenoid contents and expression of related genes in carrot taproots - Rong-Rong Zhang; Ya-Hui Wang; Tong Li; Guo-Fei Tan; Jian-Ping Tao; Xiao-Jun Su; Zhi-Sheng Xu; Yong-Sheng Tian; Ai-Sheng Xiong (Protoplasma, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Correlation of exosomal microRNA clusters with bone metastasis in non-small cell lung cancer - Xiao-Rong Yang; Can Pi; Ruoying Yu; Xiao-Jun Fan; Xiao-Xiao Peng; Xu-Chao Zhang; Zhi-Hong Chen; Xue Wu; Yang Shao; Yi-Long Wu; Qing Zhou (Clinical & Experimental Metastasis, 2021)
20–40% of lung cancer patients develop bone metastasis (BM) with significantly decreased overall survival. Currently, BM is mainly diagnosed by computerized tomography (CT) scan or magnetic resonance imaging (MRI) when symptom develops. Novel biomarkers with higher prediction value of BM are needed. Plasma-derived exosomal microRNAs had been isolated and sequenced of total 30 non-small cell lung cancer (NSCLC) patients including 16 with bone metastasis and 14 without bone metastasis. Hierarchical clustering based on the total miRNA profile can clearly separate cancer patients and healthy individuals (H), but not patients with (BM +) or without (BM−) BM. Weight Co-expression network of miRNAs (WGCNA) analyses identified three consensus clusters (A, B, C) of highly correlated miRNAs, among which cluster B (144 miRNAs) showed significantly differential expression in lung cancer patients, especially in BM + group. Pathway analysis of cluster B miRNAs revealed enrichment in metabolic pathways that may involve in preconditioning of the metastatic niche. Three differentially expressed miRNAs between BM + and BM− patients within cluster B were identified as miR-574-5p, a suppressor of Wnt/β-catenin pathway, was down-regulated, while miR-328-3p and miR-423-3p, two activators of the same pathway, were up-regulated in BM + patients. Cluster A miRNAs (n = 49) also showed trend of upregulation in BM + patients. Interestingly, pathway analysis indicated that 43 of them are associated with chromosome14, which has been suggested to promote epithelial-mesenchymal transition (EMT) and bone metastasis.

Infestation and distribution of gamasid mites on Himalayan field rat (Rattus nitidus) in Yunnan Province of Southwest China - Rong Xiang; Xian-Guo Guo; Cheng-Fu Zhao; Rong Fan; Ke-Yu Mao; Zhi-Wei Zhang; Xiao-Bin Huang (Biologia, 2021)

Correction of seismic attribute-based small-structure prediction errors using GPR data—A case study of the Shuguang Coal Mine, Shanxi - Cui Fan; Zhao Zhi-Rong; Du Yun-Fei; Bai Yu; Xu Chang-Qing; Jia Xiao-Feng (Applied Geophysics, 2020)

Vallicoccus soli gen. nov., sp. nov., a novel actinobacterium isolated from soil, and description of Vallicoccaceae fam. nov., Motilibacterales ord. nov. - Yu-Zhou Feng; Wei-Xun Chunyu; Rui Liang; Richard L. Hahnke; Peter Schumann; Yu-Rong Zhao; Sheng Gao; Min Yin; Yang Ji; Le Sun; Xiao-Yang Zhi; Shu-Kun Tang (Antonie van Leeuwenhoek, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

Microencapsulated β-carotene preparation using different drying treatments - Xiang-yu Li; Mian-bin Wu; Min Xiao; Shu-huan Lu; Zhi-ming Wang; Jian-ming Yao; Li-rong Yang (Journal of Zhejiang University-SCIENCE B, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Effect of Apolipoprotein E Genotypes on Huntington’s Disease Phenotypes in a Han Chinese Population - Xiao-Yan Li; Yan-Bin Zhang; Miao Xu; Hong-Rong Cheng; Yi Dong; Wang Ni; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2019)

QTL analysis of delayed maize flowering in response to low phosphate across multi-environments - Zhiyong Ren; Xiao Zhang; Hailan Liu; Wenjun Liu; Zhi Nie; Dan Liu; Ling Wu; Haijian Lin; Shunzong Su; Duojiang Gao; Bowen Luo; Peng Ma; et al. (Euphytica, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

Reduced thiamine binding is a novel mechanism for TPK deficiency disorder - Wenjie Huang; Jiao Qin; Dingdong Liu; Yan Wang; Xiaofei Shen; Na Yang; Hui Zhou; Xiao-Tang Cai; Zhi-Ling Wang; Dan Yu; Rong Luo; Qingxiang Sun; et al. (Molecular Genetics and Genomics, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

A frameshift mutation in exon 19 of MLH1 in a Chinese Lynch syndrome family: a pedigree study - Qiao-qi Sui; Wu Jiang; Xiao-dan Wu; Yi-hong Ling; Zhi-zhong Pan; Pei-rong Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Effect of Co-overexpression of Nisin Key Genes on Nisin Production Improvement in Lactococcus lactis LS01 - Zhi-Jian Ni; Xiao-yuan Zhang; Fei Liu; Miao Wang; Rong-hua Hao; Pei-xue Ling; Xi-Qiang Zhu (Probiotics and Antimicrobial Proteins, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Trichoderma harzianum-induced resistance against Fusarium oxysporum involves regulation of nuclear DNA content, cell viability and cell cycle-related genes expression in cucumber roots - Shuang-Chen Chen; Hong-Jiao Zhao; Zhong-Hong Wang; Cai-Xia Zheng; Pu-Yan Zhao; Zhi-Hua Guan; Hai-Yang Qin; Ai-Rong Liu; Xiao-Min Lin; Golam-Jalal Ahammed (European Journal of Plant Pathology, 2017)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

A Fluorescence Immunochromatographic Assay Using Europium (III) Chelate Microparticles for Rapid, Quantitative and Sensitive Detection of Creatine Kinase MB - Xiao-Hong Lai; Rong-Liang Liang; Tian-Cai Liu; Zhi-Ning Dong; Ying-Song Wu; Lin-Hai Li (Journal of Fluorescence, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Soil washing in combination with homogeneous Fenton-like oxidation for the removal of 2,4,4′-trichlorodiphenyl from soil contaminated with capacitor oil - Xiao-Hong Ma; Ling Zhao; Zhi-Rong Lin; Yuan-Hua Dong (Environmental Science and Pollution Research, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Paenibacillus populi sp. nov., a novel bacterium isolated from the rhizosphere of Populus alba - Tong-Yan Han; Xiao-Mei Tong; Yan-Wei Wang; Hui-Min Wang; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Multilocus sequence typing analysis of Cronobacter spp. isolated from China - Jing-Hua Cui; Xiao-Li Du; Rong-Jie Wei; Hai-Jian Zhou; Wei Li; Stephen Forsythe; Zhi-Gang Cui (Archives of Microbiology, 2015)

Paenibacillus vini sp. nov., isolated from alcohol fermentation pit mud in Sichuan Province, China - Xiao-Rong Chen; Cheng-Bin Shao; Yan-Wei Wang; Ming-Xiong He; Ke-Dong Ma; Hui-Min Wang; De-Long Kong; Xiang Guo; Yi-Qing Zhou; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Characterization of the biological properties and complete genome sequence analysis of a cattle-derived rabies virus isolate from the Guangxi province of southern China - Hai-Bo Tang; Zhuan-Ling Lu; Yi-Zhi Zhong; Xiao-Xia He; Tao-Zhen Zhong; Yan Pan; Xian-Kai Wei; Yang Luo; Su-Huan Liao; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Light-regulated phosphorylation of maize phosphoenolpyruvate carboxykinase plays a vital role in its activity - Qing Chao; Xiao-Yu Liu; Ying-Chang Mei; Zhi-Fang Gao; Yi-Bo Chen; Chun-Rong Qian; Yu-Bo Hao; Bai-Chen Wang (Plant Molecular Biology, 2014)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Expression of yeast acyl-CoA-∆9 desaturase leads to accumulation of unusual monounsaturated fatty acids in soybean seeds - Jin-Ai Xue; Xue Mao; Zhi-Rong Yang; Yong-Mei Wu; Xiao-Yun Jia; Li Zhang; Ai-Qin Yue; Ji-Ping Wang; Run-Zhi Li (Biotechnology Letters, 2013)

The Very Large G Protein Coupled Receptor (Vlgr1) in Hair Cells - Jin-Peng Sun; Rong Li; Hong-Ze Ren; An-Ting Xu; Xiao Yu; Zhi-Gang Xu (Journal of Molecular Neuroscience, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

PTP1B inhibitor improves both insulin resistance and lipid abnormalities in vivo and in vitro - Yi-ming Ma; Rong-ya Tao; Qian Liu; Juan Li; Jin-ying Tian; Xiao-lin Zhang; Zhi-yan Xiao; Fei Ye (Molecular and Cellular Biochemistry, 2011)

Discovering the distinct inhibitory effects between C4-epimeric glycosyl amino acids: new insight into the development of protein tyrosine phosphatase inhibitors - Xiao-Peng He; Cui Li; Zhi-Zhou Wang; Li-Xin Gao; Xiao-Xin Shi; Yun Tang; Juan Xie; Jia Li; Guo-Rong Chen; Kaixian Chen (Glycoconjugate Journal, 2011)

Complete genome sequence of a tomato spotted wilt virus isolate from China and comparison to other TSWV isolates of different geographic origin - Zhong-Ze Hu; Zhi-Ke Feng; Zhi-Jun Zhang; Yao-Bin Liu; Xiao-Rong Tao (Archives of Virology, 2011)

Changes of Curdlan Biosynthesis and Nitrogenous Compounds Utilization Characterized in ntrC Mutant of Agrobacterium sp. ATCC 31749 - Li-Jun Yu; Jian-Rong Wu; Zhi-Yong Zheng; Xiao-Bei Zhan; Chi Chung Lin (Current Microbiology, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

Kinetic analysis of γ-glutamyltransferase reaction process for measuring activity via an integration strategy at low concentrations of γ-glutamyl p-nitroaniline - Zhi-rong Li; Yin Liu; Xiao-lan Yang; Jun Pu; Bei-zhong Liu; Yong-hua Yuan; Yan-ling Xie; Fei Liao (Journal of Zhejiang University-SCIENCE B, 2011)

Improvement of the CuZn-superoxide dismutase enzyme activity and stability as a therapeutic agent by modification with polysialic acids - Jian Rong Wu; Yi Lin; Zhi Yong Zheng; Chi Chung Lin; Xiao Bei Zhan; Ying Qiang Shen (Biotechnology Letters, 2010)

Effects of erythromycin on voriconazole pharmacokinetics and association with CYP2C19 polymorphism - Hui-Yan Shi; Jin Yan; Wen-Hui Zhu; Guo-Ping Yang; Zhi-Rong Tan; Wei-Hua Wu; Gan Zhou; Xiao-Ping Chen; Dong-Sheng Ouyang (European Journal of Clinical Pharmacology, 2010)

Diversity and Antimicrobial and Plant-Growth-Promoting Activities of Endophytic Fungi in Dendrobium loddigesii Rolfe - Xiao Mei Chen; Hai Ling Dong; Ke Xing Hu; Zhi Rong Sun; Juan Chen; Shun Xing Guo (Journal of Plant Growth Regulation, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

Association of functional polymorphisms in MMPs genes with gastric cardia adenocarcinoma and esophageal squamous cell carcinoma in high incidence region of North China - Yan Li; Dong-lan Sun; Ya-nan Duan; Xiao-juan Zhang; Na Wang; Rong-miao Zhou; Zhi-feng Chen; Shi-jie Wang (Molecular Biology Reports, 2010)

Association of TNFAIP3 polymorphism with rheumatic heart disease in Chinese Han population - Rong Hua; Ji-bin Xu; Jiu-cun Wang; Li Zhu; bing Li; Yang Liu; Sheng-dong Huang; Li Jin; Zhi-yun Xu; Xiao-feng Wang (Immunogenetics, 2009)

Suppression of neuronal excitability by the secretion of the lamprey (Lampetra japonica) provides a mechanism for its evolutionary stability - Shaopeng Chi; Rong Xiao; Qingwei Li; Liwei Zhou; Rongqiao He; Zhi Qi (Pflügers Archiv - European Journal of Physiology, 2009)

Development of the male reproductive structures in Taxus yunnanensis - Bing-Yi Wang; Jian-Rong Su; Danilo D. Fernando; Zong-Hui Yang; Zhi-Jun Zhang; Xiao-Ming Chen; Yan-Ping Zhang (Plant Systematics and Evolution, 2008)

Sorption of 1,1,1-trichloro-2,2-bis(p-chlorophenyl) ethane (DDT) by clays and organoclays - Rong-Ling Dai; Gang-Ya Zhang; Xiao-Zhi Gu; Ming Kuang Wang (Environmental Geochemistry and Health, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Resistin does not down-regulate the transcription of insulin receptor promoter - Xiao-zhi Qiao; Xian-feng Wang; Zhe-rong Xu; Yun-mei Yang (Journal of Zhejiang University-SCIENCE B, 2008)

Persistence and dissipation of synthetic pyrethroid pesticides in red soils from the Yangtze River Delta area - Xiao-zhi Gu; Gang-ya Zhang; Li Chen; Rong-ling Dai; Yuan-chun Yu (Environmental Geochemistry and Health, 2008)

Polymorphisms in intron 1 of the porcinePOU1F1 gene - Cheng-Yi Song; Bo Gao; Shang-Hui Teng; Xiao-Yang Wang; Fei Xie; Guo-hong Chen; Zhi-Yue Wang; Rong-bin Jing; Jiu-De Mao (Journal of Applied Genetics, 2007)

Development and evaluation of immunoassay for zeranol in bovine urine - Yuan Liu; Cun-zhen Zhang; Xiang-yang Yu; Zhi-yong Zhang; Xiao Zhang; Rong-rong Liu; Xian-jin Liu; Zhen-ming Gong (Journal of Zhejiang University-SCIENCE B, 2007)

Relationship between resistin level in serum and acute coronary syndrome or stable angina pectoris - Xiao-zhi Qiao; Yun-mei Yang; Zhe-rong Xu; Li-ai Yang (Journal of Zhejiang University-SCIENCE B, 2007)

Morphological changes of cholinergic nerve fibers in the urinary bladder after establishment of artificial somatic-autonomic reflex arc in rats - Han-Zhi Wang; Shu-Rong Li; Can Wen; Chuan-Guo Xiao; Bing-Yin Su (Neuroscience Bulletin, 2007)

Phenotypic plasticity rather than locally adapted ecotypes allows the invasive alligator weed to colonize a wide range of habitats - Yu-Peng Geng; Xiao-Yun Pan; Cheng-Yuan Xu; Wen-Ju Zhang; Bo Li; Jia-Kuan Chen; Bao-Rong Lu; Zhi-Ping Song (Biological Invasions, 2007)

Molecular cloning and characterization of betaine aldehyde dehydrogenase gene from Suaeda liaotungensis and its use in improved tolerance to salinity in transgenic tobacco - Qiu-Li Li; Xiao-Rong Gao; Xiao-Hong Yu; Xing-Zhi Wang; Li-Jia An (Biotechnology Letters, 2003)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)